2016
DOI: 10.18632/oncotarget.12164
|View full text |Cite
|
Sign up to set email alerts
|

MMP-1 promoter polymorphism is associated with risk of radiation-induced lung injury in lung cancer patients treated with radiotherapy

Abstract: Matrix metalloproteinase-1 (MMP-1) has been implicated in several inflammatory and fibrotic diseases. We hypothesized that genetic variations in the MMP1 promoter region are associated with risk of radiation-induced lung injury (RILI). A cohort of 251 lung cancer patients was genotyped for five single nucleotide polymorphisms in the MMP1 promoter region. We found that rs1144393 AG/GG was strongly correlated with an increased occurrence of grade ≥ 2 RILI (p = 0.002). Additionally, patients with the rs1144393 AG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
(28 reference statements)
1
11
0
Order By: Relevance
“…Our study suggested that the rs7242 polymorphism can be used as a predictor of RP. In combination with our previous findings concerning RP susceptibility and SNPs in TGFβ1, ITGB6, PI3CA, AKT2 , and MMP1 , we can establish a more accurate model using these variants, enabling the prediction of RP by genotyping patients prior to radiotherapy. This would enable patients lacking RP susceptibility genotypes to receive appropriately elevated radiation doses to enhance tumor‐related therapies.…”
Section: Discussionmentioning
confidence: 68%
“…Our study suggested that the rs7242 polymorphism can be used as a predictor of RP. In combination with our previous findings concerning RP susceptibility and SNPs in TGFβ1, ITGB6, PI3CA, AKT2 , and MMP1 , we can establish a more accurate model using these variants, enabling the prediction of RP by genotyping patients prior to radiotherapy. This would enable patients lacking RP susceptibility genotypes to receive appropriately elevated radiation doses to enhance tumor‐related therapies.…”
Section: Discussionmentioning
confidence: 68%
“…This evidence from knockout mice models strongly suggested that MMP-8 may play a protective role against carcinogenesis (24,25). Furthermore, there exist certain positive epidemiological findings, which reported that genotypes of promoter regions of other MMPs such as MMP-1 and MMP-9, may serve as promising markers for the prediction of lung cancer susceptibility and prognosis (26)(27)(28). From the viewpoint of protein expression and function, elevated MMP-8 might increase cell adhesion by rearrangement of cytoskeleton actin, thus decreasing cell invasion (29).…”
Section: Discussionmentioning
confidence: 94%
“…Second, the mutant mice deficient in MMP-8 were more susceptible to develop skin cancer (27,28). From the viewpoint of a genomic study, some positive epidemiological findings reported that genotypes of promoter region of other MMPs such as MMP-1 and MMP-9, may serve as promising markers for the prediction of lung cancer susceptibility and prognosis (29)(30)(31). From the molecular viewpoint, MMP-8 might increase cell adhesion by rearrangement of cytoskeleton actin, thus decreasing cell invasion (32).…”
Section: Discussionmentioning
confidence: 99%